Scorpionate‐Type Coordination in MFU‐4l Metal–Organic Frameworks: Small‐Molecule Binding and Activation upon the Thermally Activated Formation of Open Metal Sites1. (20th May 2014) - Denysenko, Dmytro; Grzywa, Maciej; Jelic, Jelena; Reuter, Karsten; Volkmer, Dirk
Abstract Postsynthetic metal and ligand exchange is a versatile approach towards functionalized MFU‐4l frameworks. Upon thermal treatment of MFU‐4l formates, coordinatively strongly unsaturated metal centers, such as zinc(II) hydride or copper(I) species, are generated selectively. CuI‐MFU‐4l prepared in this way was stable under ambient conditions and showed fully reversible chemisorption of small molecules, such as O2, N2, and H2, with corresponding isosteric heats of adsorption of 53, 42, and 32 kJ mol−1, respectively, as determined by gas‐sorption measurements and confirmed by DFT calculations. Moreover, CuI‐MFU‐4l formed stable complexes with C2H4 and CO. These complexes were characterized by FTIR spectroscopy. The demonstrated hydride transfer to electrophiles and strong binding of small gas molecules suggests these novel, yet robust, metal–organic frameworks with open metal sites as promising catalytic materials comprising earth‐abundant metal elements.